Keberhasilan Program Kawasan Rumah Pangan Lestari (KRPL) pada Kelompok Wanita Tani di Kabupaten Gianyar - Sugitarina, I Gusti Ayu Dwi; Darmawan, Dwi Putra; Astiti, Ni Wayan Sri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 2 (2016): Vol. 4 - No. 2 - Oktober 2016, 2016)
The rate of population growthand theconversion of agricultural land that will never be stopped . E fforts were made to keep striving for food availability by optimizing the utilization ofthe yard. The Ministry of Agriculture initiated the optimization of theutilization of the yard through KRPL program . KRPL program emphasizeson meeting the food need sat the household level by involving KWT. The purpose of this study was to analyze the influence ofthe characteristics of women farme s to KRPL program's success in Gianyar, knowing the perception of women farmers to KRPL program in Gianyar, and analyzing the success of the program KRPL to increase drevenue and improved family nutrition in a group of  women  farmersin Gianyar. This research was conducted in Gianyarwith a population of KWT  members KRPL program beneficiaries in 2013. Determination of the number of respondents by Slovin method with the number of respondentsas many as 58 people , while the technique of making respondents using proportional method. Data collection techniques include: interviews, observation and documentation, while the relationship between the construc analyzed by PLS-SEM. The results showed thatthe characteristicsof women farmers which include: age , formal education and non-formal education has apositive influence on the success of the program KRPL in Gianyar. Perceptionof KWT on the implementation and success of the program KRPL in Gianyar is very well . KRPL program implementation have a positive impact on household income and family nutrition improvement in the group of women farmers in Gianyar. It can beseen from the PPH in the research location of 71. 5 , and an average gain o fKRPL Rp. 48 448/month. Suggestion that san be summited:(1) KWT is expected to improve knowledge about balanced nutrition for the famil ies so that diversification of food consumption and nutrition can be realized . Technica l institutions such as the Department of Agriculture , Plantation and Forestry, and the Departmentof Industryand Trade ofthe Gianyar regency need to provide technical guidance (technical guidance) on post-harvest handling and the development of domesticindustr y; ( 2) KWT order to improve the application of technology and techniques of planting so that optimal utilization of the yard; ( 3) KRPL program success is expected to continue to be sustainableing maintaining the utilization of the yardand the preservation of local food crops fo rthe future o fsustainable and diversification
Keywords: RegionSustainable Food Houses, groupsof women farmers, andSuccessProgram